Pengayaan kompetensi mahasiswa melalui Penelitian Tindakan Kelas - Syamsidah Syamsidah; Ratnawati T. (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
Classroom Action Research (CAR) Training is one of Community Service programs which aims to help studentsof Home Economics Department who are highly interested inconducting CAR as their undergraduate thesis method.Meanwhile, this subject has been changed into GeneralResearch Methodology. This training involved twenty studentsof Home Economics Department in Faculty of Engineering ofUniversitas Negeri Makassar. Method used in this trainingwere lecturing, question and answer session, and discussion.This Community Service Program aims to: 1) improvestudents’ understanding on CAR, 2) improve students’creativity in constructing research titile and research problems,3) improve students ability in developing research backgroundand research purposes, 4) improve students’ ability inreviewing literature and selecting hypothesis, 5) improvestudents’ ability in choosing data collection technique andcycle in CAR, 6) improve students’ ability in analyzing thecollected data, 7) improve students ability in writing CARproposal. After conducting CAR Training to twenty students,the result showed that students understand well how to writegood CAR proposal, choose research gap, formulateappropriate research title, purposes, reviewing literature,hypothesis, research framework, and research method. Theparticipants not only can write good CAR proposal butinspired to re-open the class of CAR as one of subjects inHome Economics Department curriculum.